Cyclodextrin formation by the thermostable alpha-amylase of Thermoanaerobacterium thermosulfurigenes EM1 and reclassification of the enzyme as a cyclodextrin glycosyltransferase. - Wind, R D (1995)
Extensive characterization of the thermostable alpha-amylase of Clostridium thermosulfurogenes EM1, recently reclassified as Thermoanaerobacterium thermosulfurigenes, clearly demonstrated that the enzyme is a cyclodextrin glycosyltransferase (CGTase). Product analysis after incubation of the enzyme with starch revealed formation of alpha-, beta-, and gamma-cyclodextrins, as well as linear sugars. The specific activity for cyclization of this CGTase was similar to those of other CGTases, whereas the specific activity for hydrolysis was relatively high in comparison with other CGTases. Alignment of the amino acid sequence of the T. thermosulfurigenes enzyme with sequences from known bacterial CGTases showed high homology. The four consensus regions of carbohydrate-converting enzymes, as well as a C-terminal raw-starch binding motif, could be identified in the sequence.